(3fJGFL eQGLYI GdcJH GdeOQSjI defGgL GdJQHjI GdUMjI hGdHjFjIs - (3eNhd, LgGOs ((3HjQhJs (3GdeQcR GdJQHhj ddHMhK hGdEfeGA (B/ (3GdjhfSch (B/ (3efXeI GdUMI GdYGdejIs, 2000)
(3jYQV gPG GdJbQjQ fJGFL OQGSI JJfGhd eQGLYI GdcJH GdeOQSjI GdLOjOI, aj GdeQGMd GdJYdjejI GdKdGK, GdJj CUOQgG GdeQcR GdJQHhj ddHMhK hGdEfeGA(B/(3hRGQI GdJQHjI hGdJYdje GdYGdj(B. (3hTedJ GdehGO GdJGdjI(B: (3GddZGJ GdYQHjI hGdaQfSjI hGdEfcdjRjI, GdQjGVjGJ, GdYdhe, GdLZQGajG, GdJQHjI GdhWfjI hGdJfTFI GdeOfjI, GdcjejGA, GdajRjGA, GdeYdheGJjI hGdJcfhdhLjG, ef MjK JLGfSgG eY GdefGgL GdQSejI ddJQHjI GdUMjI hGdHjFjI(B. (3EYJeOJ GdOQGSI Ydi ebGQfI eMJhjGJ efGgL GdcJH (B((3cJGH GdJdejP, Odjd GdeYde, OaJQ GdJeGQjf aj MGd hLhOg(B) (3dcd eGOI ef fGMjI UMI GdfUhU hGdUhQ GdeQGabI dgG, EHJOGkA ef GdUa GdChd, Ke OqhfJ GdedGMXGJ Mhd GdfUhU hGdUhQ dcd cJGH aj ESJeGQGJ(B. (3HjfJ GdfJGFL YOe hLhO JLGfS JGe aj JOQL WQM GdehGVjY GdPj jHOC ef GdUaha GdChdi Edi GdJGSYI, aHYV GdehGVjY GdeJfGhdI aj YOO ef GdUaha GdChdi ZGFHI JeGeG aj GdUaha GddGMbI, hCNQi de JJfGhdgG GdefGgL EdG aj GdeQGMd GdCNjQI(B. (3ceG Cf bdI GdJOQL HGdehGVjY hYOe eJGHYI GdCacGQ GdQFjSjI YHQ GdeQGMd GdJYdjejI jaqhJ Ydi GdWGdH GdedJMb HGdefGgL GdLOjOI GdcKjQ ef GdehGVjY GdJj SHb WQMgG aj GdeQGMd GdSGHbI, hGdJdGejP GdPjf EcJSHhG eYdheGJ Ch egGQGJ UMjI hHjFjI aj GdeQGMd GdChdi jJYQVhf dabOGfgG EPG de jSJeQ WQMgG dGMbG(B. (3HGdEVGaI Edi hLhO HYV GdCgOGa GdJj djS dgG YdGbI hGVMI HGdeGOI GdJj oCONdJ EdjgG, eeG jTjQ Edi GfYOGe hLhO GdQDjI GdHjFjI hGdUMjI GdeJfGSbI dHYV GdehGO, hHYV GdCgOGa GdJj JYJHQ HSjWI ebGQfI HYeQ GdJdejP aj GdUaha GdYdjG ef GdeQMdI GdOQGSjI(B.s
(3GdfhY (B: (3JbQjQs
Keywords: (3GdJQHjI GdUMjIs; Education Sanitaire; Health education; Livres Scolaires; Textbooks; (3GdcJGH GdeOQSjs